Preoperative Systemic Therapy Versus Upfront Surgery in HER2-Positive Breast Cancer in the Real World - Yu, Xingfei; Wang, Chen; Zheng, Yabing; Miao, Beibei; Hu, Jiejie; Shao, Xiying; Sheng, Liming; Lin, Juan; Ding, Yuqin; Xuan, Haojun; Ding, Yingying; Gong, Lijie; et al. (Frontiers in Oncology, 2021)
Purpose To compare survival in different strategies, preoperative systemic treatment versus upfront surgery, in HER2-positive early breast cancer patients in the real world. Methods According to the actual upfront treatment, eligible patients from 2012 to 2015 were classified as preoperative systemic treatment or upfront surgery group prospectively. The primary endpoint is disease-free survival; the second endpoint is overall survival. All the outcomes were examined in the propensity score matching model and inverse probability of treatment weighting model. Results Included in the analysis were 1,067 patients (215 in the preoperative systemic treatment group, 852 in the upfront surgery group). In the propensity score matching model (matching at 1:1 ratio), the disease-free survival of the preoperative systemic treatment group was significantly higher than that of the upfront surgery group (hazard ratio, 0.572, 95%CI, 0.371–0.881, P, 0.012). In the inverse probability of treatment weighting model, there was no significant difference in disease-free survival between the two groups (hazard ratio, 0.946, 95%CI, 0.763–1.172, P, 0.609). For overall survival, there was no significant difference between the two groups. Conclusion The HER2-positive patients who accepted preoperative systemic treatment had better disease-free survival than those who underwent upfront surgery by real-world statistic methods. Clinical Trial Registration Clinicaltrials.gov, identifier NCT04249440.